WRITING AS AN INVESTMENT TO FULFILL AN INCREASE IN THE FUNCTIONAL POSITION OF LECTURER - Julinda Siregar; Hotmaulina Sihotang (PT. Anagata Sembagi Education, 2024)
Scientific writing has an essential role in supporting the improvement of lecturers' functional positions, where scientific publications are seen as a form of strategic investment that can encourage academic career development. Through publications, lecturers not only share their research results and intellectual ideas, but also increase their competence, credibility, and professional recognition in the world of higher education. This study aims to analyze scientific writing as a long-term investment that plays a role in fulfilling the requirements for lecturers' functional promotion, and to assess the impact of writing productivity on institutional recognition. Using qualitative methods, this study identifies motivational factors, challenges, and benefits obtained by lecturers through scientific writing and publication activities. The results of the analysis show that scientific writing productivity significantly contributes to the process of functional promotion, both through increasing the required credit score, as well as through wider recognition of lecturers' scientific contributions in the academic sphere. Thus, scientific writing and publication skills need serious attention in lecturer development programs, so that they can support the improvement of professional performance and strengthen the academic position of lecturers in higher education. Continuous efforts in improving scientific writing skills are seen as crucial as a form of investment for the future of lecturers' academic careers, which in turn can contribute to improving the quality of higher education in Indonesia.